A matched employer-employee panel data set for Austria: 2002 - 2005 - Inga Freund; Bernhard Mahlberg; Alexia Prskawetz (Vienna University of Technology, Institute of Mathematical Methods in Economics, Research Group Economics, 2011)
Matched employer-employee (panel) data sets are gaining increasing importance in the analysis of labour markets. In collaboration with Statistics Austria we recently initiated the set up of a matched employer-employee panel data set for Austria, which covers the years 2002-2005. The aim of the paper is to introduce the data set to a broader audience. We first present the set up of the panel data, indicating in more detail the data sources and matching procedure underlying the matched employer-employee data set for Austria. In a second step we show descriptive statistics of the main variables included in our data set. These various statistics encompass three levels of analysis: the aggregate level (i.e. the entire sample), firm level and individual (employee) level. – – Verknüpfte Arbeitgeber-Arbeitnehmer (Panel-) Datensätze gewinnen in der Analyse von Arbeitsmärkten zunehmend an Bedeutung. In Zusammenarbeit mit Statistik Austria haben wir den Aufbau eines verknüpften Arbeitgeber- Arbeitnehmer Panel-Datensatzes für Österreich über die Jahre 2002 bis 2005 initiiert. Das Ziel dieses Artikels ist es, diesen Datensatz einem größeren Publikum gegenüber bekannt zu machen. Zunächst stellen wir dessen Aufbau vor, wobei wir explizit sowohl auf die zugrunde liegenden Datenquellen als auch die Verknüpfungsprozedur eingehen. In einem weiteren Schritt präsentieren wir deskriptive Statistiken der im Datensatz enthaltenen Kernvariablen. Zu diesem Zweck betrachten wir drei unterschiedliche Analyseebenen: die Stichprobe als Ganzes, die Firmenebene sowie das einzelne Individuum.
Keywords: 330; Workforce characteristics; Firm characteristics; Linking of data; Economic structure; Structural business statistics; Data of social security; Data of wage tax